2022
DOI: 10.3390/sports10100142
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Acute Effects of the Daily Mile™ vs. Shuttle Runs on Children’s Cognitive and Affective Responses

Abstract: Background: This study investigated the acute effects of two physical activity (PA) bouts on children’s cognitive and affective responses. Methods: Twenty-nine participants (16 boys and 13 girls; Mage = 9.34 years, SD = 0.48), using a within-subjects crossover design, performed three 15-minute conditions: (a) TDM—The Daily Mile™; (b) 12 repeated 30–45-second shuttle runs at ≥ 85% HRMAX; and (c) a sedentary control condition. Cognitive performance (i.e., Stroop, Digit Span, and Corsi blocks) was measured before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…The Stroop test was used to assess the children’s inhibitory control. The test has been widely used in studies investigating the effects of PA on the inhibition in children [ 49 , 50 , 51 , 52 ]. The test was administered using PsyToolkit [ 53 , 54 ]: an online coding tool that allowed us to design and deliver the cognitive tests entirely online.…”
Section: Methodsmentioning
confidence: 99%
“…The Stroop test was used to assess the children’s inhibitory control. The test has been widely used in studies investigating the effects of PA on the inhibition in children [ 49 , 50 , 51 , 52 ]. The test was administered using PsyToolkit [ 53 , 54 ]: an online coding tool that allowed us to design and deliver the cognitive tests entirely online.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the authors concluded that short bouts of just 6-10 min of VPA were sufficient to enhance inhibition (ES = 0.24), making VPA particularly time-efficient. Importantly, intermittent short exercise bouts have been suggested as a more effective way to target children's cognition, as these more closely mimic their naturally occurring patterns of activity (Martins et al, 2022). In a metaanalysis of high intensity interval training (HIIT) interventionsby its very nature an intermittent exercise protocol, consisting of short bouts of very high intensity exercise at >85% of maximal heart rate- Leahy et al (2020) found even greater positive effects [standardized mean difference (SMD) = 0.50] of intermittent VPA for general EF.…”
Section: Introductionmentioning
confidence: 99%
“…Another small number of studies carried out with children show that low to high-intensity physical activity provides immediate gains in executive function [ 29 , 30 ]. Nevertheless, few studies have delved into determining the optimal level of PA that exerts the highest impact on CP among adolescents.…”
Section: Introductionmentioning
confidence: 99%